A Review of Current Clinical Concepts in the Pathophysiology, Etiology, Diagnosis, and Management of Hypercalcemia - Tonon, Carolina Rodrigues [UNESP]; Silva, Taline Alisson Artemis Lazzarin [UNESP]; Pereira, Filipe Welson Leal [UNESP]; Queiroz, Diego Aparecido Rios [UNESP]; Favero Junior, Edson Luiz [UNESP]; Martins, Danilo [UNESP]; Azevedo, Paula Schimdt [UNESP]; Okoshi, Marina Politi [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Polegato, Bertha Furlan [UNESP] (International Scientific Information, 2022)
Calcium is the most abundant extracellular cation in the body, and it is responsible for structural and enzymatic functions. Calcium homeostasis is regulated by 3 factors: Calcitonin, vitamin D, and parathyroid hormone (PTH). Hypercalcemia is defined by a serum calcium concentration >10.5 mg/dL, and it is classified into mild, moderate, and severe, depending on calcium values. Most cases are caused by primary hyperparathyroidism and malignancies. Various mechanisms are involved in the pathophysiology of hypercalcemia, such as excessive PTH production, production of parathyroid hormone-related protein (PTHrp), bone metastasis, extrarenal activation of vitamin D, and ectopic PTH secretion. The initial approach is similar in most cases, but a definitive treatment depends on etiology, that is why etiological investigation is mandatory in all cases. The majority of patients are asymptomatic and diagnosed during routine exams; only a small percentage of patients present with severe manifestations which can affect neurological, muscular, gastrointestinal, renal, and cardiovascular systems. Clinical manifestations are related to calcium levels, with higher values leading to more pronounced symptoms. Critically ill patients should receive treatment as soon as diagnosis is made. Initial treatment involves vigorous intravenous hydration and drugs to reduce bone resorption such as bisphosphonates and, more recently, denosumab, in refractory cases; also, corticosteroids and calcitonin can be used in specific cases. This review aims to provide a clinical update on current concepts of the pathophysiology of calcium homeostasis, epidemiology, screening, clinical presentation, diagnosis, and management of hypercalcemia.
Keywords: Calcium; Diphosphonates; Humoral Hypercalcemia of Malignancy; Hypercalcemia; Hyperparathyroidism